(3bOhI GdeQjO GdefjH HCNdGb GdfHi GdMHjHs - (3Ydj Hf ejehf Hf CHj HcQ Hf jhSa GdgGTej GdMSfj GdEOQjSj GdaGSj GdeZQHj, GHf ejehf , CHh GdMSf,J (B917 (3g` s ((3YHO GdhgGH Hf SdjeGf Hf YHO GdhgGH GdghT s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje jbhd GdYHO GdabjQ Ydi Hf ejehf Hf CHj HcQ ONd Ydi HYV GdENhGf hHjOg hQbI cGZO ecJhH ajgG MOjK PcQ di Cfg ef CMGOjK GdeUGHjM s
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG eMeO hYdi Bdg eG OGe Gdedc ddg hGdYR hGdHbGA hMSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B741s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs